Improving nutrient uptake in sugar beet - Alshmam, Amar (2020)
Improving nutrient use efficiency in sugar beet is important to increase sugar production, lower the use of chemical fertilizers, keep the environment clean and reduce production costs. The need for effective and feasible methods for obtaining better yields which meet the global demand for sugar has become increasingly important. The aim of this thesis was to explore different ways of improving nutrient uptake in sugar beet using a combination of glasshouse and field experiments. Firstly, the effect of mycorrhizal fungi as a bio-fertilizer was investigated. Secondly, the effect phosphate solubilizing bacteria (PSB) especially (Bacillus sp.), in combination with different rates of rock phosphate as a source of phosphate, was explored. A third glasshouse experiment looked at the effect of slow-release phosphate fertilizer on the growth of sugar beet. Finally, a number of field experiments were designed to investigate if placing nitrogen (N) fertilizer at sowing improved nutrient uptake compared to the standard practice of broadcasting. No evidence of a positive relationship between sugar beet and mycorrhiza was found. However, sugar beet did respond positively to phosphate solubilizing bacteria (PSB) especially (Bacillus sp.) as a bio-fertilizer under different rates of rock phosphate as a source of phosphate. Adding of phosphate in the early stages of germination in a slow-release fertilizer form did not give the plant enough phosphate at the beginning of germination, thus getting weakly plants. However, sugar beet did respond positively to the mixture of slow-release fertilizers and soluble fertilizers in water at a rate of 45 kg P ha-1 divided into (25% CG as a slow release phosphorus fertilizer + 75% TSP as water-soluble fertilizers). Rock phosphate as non-water-soluble fertilizers had a limited effect on the growth of sugar beet without microorganisms. For the crop to benefit from the application of rock phosphate in the short term, must be activation by the microorganism in soil especially which that live free in the soil (such as bacteria; Bacillus sp.) as a bio-fertilizers. The results of N placement experiment showed that the presence of N in the early stages was sufficient to promote canopy closure, root growth, and sucrose production regardless of the method of addition. However, this study is insufficient to adopt this finding, because of some limitation such as; the emergence of the disease and its association with N fertilizer, the warm, wet conditions and a large amount of soil organic matter (N) in this area could increase N mineralization from the organic matter and also the soil content of N may be enough for plant growth.